2007
DOI: 10.1007/s00246-007-9049-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vascular Endothelial Growth Factor C–634 G Polymorphism in Taiwanese Children With Kawasaki Disease

Abstract: High expression of circulating vascular endothelial growth factor (VEGF) has been reported in patients with Kawasaki disease (KD). In the pathophysiology of KD, VEGF is considered to be involved, especially in the development of coronary artery lesions. This study aimed to examine whether the VEGF-634 promoter polymorphism is a marker of KD susceptibility or severity in Chinese patients in Taiwan. The study included 93 KD patients and 96 normal control subjects. Genotype and allelic frequencies for the VEGF ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…30 Although several other groups have studied other combinations of HLA subtypes, no consistent association has been detected so far. Considering that no significant linkage was detected near the 6p region in our genome-wide linkage analysis, 31 34 and MCP-1 35 ), hematopoietins (interleukin-4 (IL-4) [36][37][38] and IL-6 39 ), IL-1 family (IL-1b, 37 IL-18, 40 and IL-1Ra 37 ), IL-10 family (IL-10 41 ), platelet-derived growth factor family (vascular endothelial growth factor (VEGF) [42][43][44][45] and VEGFR2 42 ), and tumor necrosis factor (TNF) family (TNF-a, 46-50 lipoteichoic acid, 47 and CD40L 51,52 ). Other candidates include plasma proteins (C-reactive protein [53][54][55] and MBL2 53,55,56 ), matrix metalloproteinase (MMP) and their inhibitors (MMP2, 58 MMP3, 57,58 MMP-9, 58 MMP-12, 58 MMP-13, 58 and tissue inhibitors of metalloproteinase-2 59 ), enzymes related to atherosclerosis (methylenetetrahydrofolate reductase (MTHFR), 60 endothelial nitric oxide synthase, 61 and inducible nitric oxide synthase 61 ), components of the renin-angiotensin system (angiotensin-converting enzyme [62][63][64][65] and AGTR1 64 ), and an unclassified group (CD14, 66 FCGR2A, 67,68 SLC11A1, 69 PLA2G7, 70 UGT1A1, 71 MICA, 72 and HMOX1 71 ).…”
Section: Candidate Gene Approachmentioning
confidence: 78%
“…30 Although several other groups have studied other combinations of HLA subtypes, no consistent association has been detected so far. Considering that no significant linkage was detected near the 6p region in our genome-wide linkage analysis, 31 34 and MCP-1 35 ), hematopoietins (interleukin-4 (IL-4) [36][37][38] and IL-6 39 ), IL-1 family (IL-1b, 37 IL-18, 40 and IL-1Ra 37 ), IL-10 family (IL-10 41 ), platelet-derived growth factor family (vascular endothelial growth factor (VEGF) [42][43][44][45] and VEGFR2 42 ), and tumor necrosis factor (TNF) family (TNF-a, 46-50 lipoteichoic acid, 47 and CD40L 51,52 ). Other candidates include plasma proteins (C-reactive protein [53][54][55] and MBL2 53,55,56 ), matrix metalloproteinase (MMP) and their inhibitors (MMP2, 58 MMP3, 57,58 MMP-9, 58 MMP-12, 58 MMP-13, 58 and tissue inhibitors of metalloproteinase-2 59 ), enzymes related to atherosclerosis (methylenetetrahydrofolate reductase (MTHFR), 60 endothelial nitric oxide synthase, 61 and inducible nitric oxide synthase 61 ), components of the renin-angiotensin system (angiotensin-converting enzyme [62][63][64][65] and AGTR1 64 ), and an unclassified group (CD14, 66 FCGR2A, 67,68 SLC11A1, 69 PLA2G7, 70 UGT1A1, 71 MICA, 72 and HMOX1 71 ).…”
Section: Candidate Gene Approachmentioning
confidence: 78%
“…In the study of Dutch KD patients, 2 SNPs other than rs2010963 showed association with KD (44). With regard to association of rs2010963 with KD or CALs, two inconsistent results were also reported by Taiwanese groups (45,46).…”
Section: Non-hla Genesmentioning
confidence: 96%
“…As for the detecting method of the VEGF +405G>C polymorphism, 19 studies used the classic method of polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), four used the MassARRAY method, and the other four chose the TaqMan method. According to the classification criteria of IMIDs, there were six studies focusing on psoriasis [13,[22][23][24][25][26], four on RA [27][28][29][30], four on KD [31][32][33][34], three on GCA [35][36][37], two on T1DM [38,39], two on BD [40,41], two on SLE [42,43], one on systemic sclerosis (SS) [44], one on psoriatic arthritis (PsA) [45], one on Graves' disease (GD) [14], and one on inflammatory bowel disease (IBD) [46]. Table 2 summarizes the meta-analysis results about the relationship between the VEGF +405G>C polymorphism and the risk of IMIDs.…”
Section: Main Characteristics Of Included Studiesmentioning
confidence: 99%
“…The studies scored from 0 to 40, based on 40 assessment items. The eligible studies were divided into three levels accordingly: low quality (0-19), moderate quality (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and high quality (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Quality Assessmentmentioning
confidence: 99%